Modification on the torque sensor based electrically assisted wheelchair with dedicated solar charger kit to enhance performance in association with the center for the rehabilitation of the paralysed - Sarker, Pronob; Bari, Nafis Al; Zim, Ishtiak Ahmad; Rafi, Md. Abdullah Al Mohaymen (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.